Calcium–calmodulin gating of a pH-insensitive isoform of connexin43 gap junctions. Issue 7 (10th April 2019) - Wei, Siyu; Cassara, Christian; Lin, Xianming; Veenstra, Richard D.
Abstract : Intracellular protons and calcium ions are two major chemical factors that regulate connexin43 (Cx43) gap junction communication and the synergism or antagonism between pH and Ca 2+ has been questioned for decades. To assess the ability of Ca 2+ ions to modulate Cx43 junctional conductance ( g j ) in the absence of pH-sensitivity, patch clamp experiments were performed on Neuroblastoma-2a (N2a) cells or neonatal mouse ventricular myocytes (NMVMs) expressing either full-length Cx43 or the Cx43-M257 (Cx43K258stop) mutant protein, a carboxyl-terminus (CT) truncated version of Cx43 lacking pH-sensitivity. The addition of 1 μM ionomycin to normal calcium saline reduced Cx43 or Cx43-M257 g j to zero within 15 min of perfusion. This response was prevented by Ca 2+ -free saline or addition of 100 nM calmodulin (CaM) inhibitory peptide to the internal pipette solution. Internal addition of a connexin50 cytoplasmic loop calmodulin-binding domain (CaMBD) mimetic peptide (200 nM) prevented the Ca 2+ /ionomycin-induced decrease in Cx43 g j, while 100 μM Gap19 peptide had minimal effect. The investigation of the transjunctional voltage ( V j ) gating properties of NMVM Cx43-M257 gap junctions confirmed the loss of the fast inactivation of Cx43-M257 g j, but also noted the abolishment of the previously reported facilitated recovery of g j from inactivating potentials. We conclude that the distal CT domain of Cx43 contributes to the V j -dependent fast inactivation and facilitated recovery of Cx43 gap junctions, but the Ca 2+ /CaM-dependent gating mechanism remains intact in its absence. Sequence-specific connexin CaMBD mimetic peptides act by binding Ca 2+ /CaM non-specifically and the Cx43 mimetic Gap19 peptide has negligible effect on this chemical gating mechanism.